Transforming Tax Compliance In Optimizing State Revenue: Innovation And Challenges In The Digital Era - Siti Zulaikhah (PT Inovasi Pratama Internasional, 2025)
This research aims to analyze the influence of digital technology adoption on the level of tax compliance in Indonesia. Using a quantitative approach, this research collected data from 200 respondents consisting of business actors, both individuals and corporations, who have implemented digital technology in their tax reporting. The analytical method used is linear regression to determine the relationship between the independent variable (digital technology adoption) and the dependent variable (tax compliance). The research results show that the adoption of digital technology, such as the use of e-filing and e-billing, has a significant positive influence on the level of tax compliance. Taxpayers who adopt digital technology tend to be more compliant in reporting and paying taxes on time. However, several challenges are still faced, such as low digital literacy and concerns regarding data security. This research concludes that increasing digital literacy and strengthening technological infrastructure is needed to optimize the benefits of adopting digital technology in the tax system. Apart from that, clearer policies regarding taxation in the digital economy sector are important in facing modern economic developments. Thus, adopting digital technology can be a strategic solution in increasing tax compliance and state revenues.